Antarctic krill under sea ice: elevated abundance in a narrow band just south of ice edge - Brierley, Andrew Stuart; Fernandes, PG; Brandon, MA; Armstrong, F; Millard, NW; McPhail, SD; Stevenson, P; Pebody, M; Perrett, J; Squires, M; Bone, DG; Griffiths, G (Science, 2002)
We surveyed Antarctic krill (Euphausia superba) under sea ice using the autonomous underwater vehicle Autosub-2. Krill were concentrated within a band under ice between 1 and 13 kilometers south of the ice edge. Within this band, krill densities were fivefold greater than that of open water. The under-ice environment has tong been considered an important habitat for krill, but sampling difficulties have previously prevented direct observations under ice over the scale necessary for robust krill density estimation. Autosub-2 enabled us to make continuous high-resolution measurements of krill density under ice reaching 27 kilometers beyond the ice edge.